The Effect of People's Business Credit (KUR) PT. Papua Regional Development Bank Sentani Branch Toward Micro Small and Medium Enterprises (MSMEs) In Jayapura District - Mugiati Mugiati (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
This study aims to determine the effect of People's Business Credit assistance and the increase in income on MSMEs. This research is quantitative research. The number of samples is 32 MSMEs that take KUR at Bank Papua Sentani Branch. The analytical tools used in this study are data quality tests and simple regression analysis. From the linear regression function above, it can be explained that the Constant Value (a) has a positive value of 15.039 and the regression coefficient value for the People's Business Credit variable has a positive value of 0.606. Obtained t table of 2.04227. And t count 3.054 2.04227 t table based on the independent variable People's Business Credit has a positive effect on the dependent variable MSMEs income. Judging from the significance of 0.005 it is 0.05 for the People's Business Credit variable. Therefore, the independent variable of People's Business Credit has a positive effect on the dependent variable MSMEs income. Thus, it can be concluded that People's Business Credit obtained from the Sentani Branch of Bank Papua is influential on the income of MSMEs in Jayapura Regency. The income of MSMEs in Jayapura Regency has increased and able to develop their businesses after using the credit.